2018
DOI: 10.1002/bjs.10753
|View full text |Cite
|
Sign up to set email alerts
|

Optimized wound closure using a biomechanical abdominal model

Abstract: These findings suggest using a small bite separation (5 mm) and large bite width (16 mm) during abdominal wound closure may be optimal. Surgical relevance Suturing techniques for midline abdominal wall incisions vary between surgeons. This experimental study suggests substantial potential for improved tissue apposition by changing the suturing approach from the traditional clinical recommendation of 10 mm for both bite separation and bite width to a bite separation of 5 mm and a bite width of 16 mm. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…On the contrary, the effects of different suture materials, suture configurations and suture length to wound length ratio on the occurrence of incisional hernia have been extensively studied [5,15]. Cooney et al found the best performing bite separation and bite width to be 5 and 16 mm, respectively, in a biomechanical abdominal wall model [16]. As they also state, this is partly in agreement with the findings of the STITCH trial.…”
Section: Discussionmentioning
confidence: 67%
“…On the contrary, the effects of different suture materials, suture configurations and suture length to wound length ratio on the occurrence of incisional hernia have been extensively studied [5,15]. Cooney et al found the best performing bite separation and bite width to be 5 and 16 mm, respectively, in a biomechanical abdominal wall model [16]. As they also state, this is partly in agreement with the findings of the STITCH trial.…”
Section: Discussionmentioning
confidence: 67%
“…14 In our study, patients underwent a modified small STITCH approach with a 5 mm separation with a 10 mm width based on evidence that a wider bite may be more beneficial. 26 The authors would now recommend the use of 3/0 PDS to fix the mesh rather than 2/0 Prolene ® as this would be absorbed. Chevrel's classic onlay mesh technique places and fixes the mesh after fascial closures.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical testing has also been performed on a variety of suture patterns where suture bite and stitch interval were varied independently (36). This study showed that the use of smaller bites (suture bites) and larger bite widths (stitch interval) provided a stronger celiotomy closure when compared to other combinations (36). In a further study, the combination of a small suture bite and a large stitch interval significantly increased the suture pullout force (35).…”
Section: Other Sbsi Combinationsmentioning
confidence: 97%
“…In this study we evaluated the bursting pressure which we believe provides a better understanding of the mechanical properties of these celiotomy closure techniques in cats. Biomechanical testing has also been performed on a variety of suture patterns where suture bite and stitch interval were varied independently (36). This study showed that the use of smaller bites (suture bites) and larger bite widths (stitch interval) provided a stronger celiotomy closure when compared to other combinations (36).…”
Section: Other Sbsi Combinationsmentioning
confidence: 99%